The role of infrastructure loan in the regional development bank - Karamoy, Herman; Tasik, Hizkia H. D. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper aims to examine the role of infrastructure loan in Indonesian regional development banks. This research further analyze the relationship between types of loan and NPL. The paper employs the approaches of simulation and panel data regression on a sample of 24 Indonesian regional development banks over 2009 to 2016. It examines the financial performance of bank that have not offering infrastructure loan. It further simulates the financial performance of the bank when infrastructure loan is offered, and compares it to the initial financial performance. The results found that the banks perform better when they provide infrastructure loan than without such loan. However, the better performance of the banks in profitability and cost management is a result of the trade-off with lower liquidity. Our finding based on panel data regression indicates that Working Capital Loan and Consumptive Loan are the main contributors to the NPL. However, there is an indication that the increased in long term loan that includes infrastructure loan able to reduce the NPL.